Pelayanan Mahasiswa Relawan Pajak dalam Membantu Wajib Pajak Mengisi SPT Tahunan di Kota Dumai - Eliza, Rispa; Suwardi, Cori Oktafiani; Junita, Weni; Nirmala, Harum; Siregar, Faradillah (Jurnal Pengabdian UNDIKMA, 2022)
The purpose of this community service is to help Dumai KPP Pratama serve taxpayers in reporting their annual tax returns. The service method used is a qualitative method and the data in this study comes from original data in the form of recapitulation results from inputting data on Tax Volunteer activities. This service activity is in the form of Annual SPT assistance services carried out by Tax Volunteers to Private Taxpayers using E-Filing. The stages of service activities include the initial planning stage, the implementation stage, and the reporting stage. Based on the evaluation results obtained from KPP Pratama Dumai, it was stated that the service program of the tax volunteer team from STIE Tuah Negeri students was considered good and very helpful. The program’s success indicator could be seen from the level of annual SPT tax reporting by taxpayers in Dumai which had increased every week. Tax volunteer activities are community service activities to assist personal taxpayers to report their annual tax returns through E-Filing.